ANALYSIS OF THE IMPACT OF LIQUIDITY, PROFITABILITY, LEVERAGE, AND DIVIDEND POLICY ON STOCK PRICES IN INFRASTRUCTURE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2022-2023 - Putri Arini Septya Agustin; Endah Supeni Purwaningsih; Aminatuzzuhro Aminatuzzuhro (Income, 2025)
This research aims to analyze the influence of Liquidity, Profitability, Leverage, and Dividend Policy on Stock Prices in infrastructure companies listed on the Indonesia Stock Exchange during the period of 2022-2023. This type of research uses statistics with a quantitative approach. Data collection techniques use documentation methods, namely collecting data from the financial statements of companies published through the official IDX website. The sample size in this study consists of 17 infrastructure companies listed on the IDX for the years 2022-2023. Purposive sampling is used as a sampling determination technique with specific criteria, and multiple regression analysis is employed. Data analysis is conducted using the SPSS software version 26. The results of the study show that partially, Liquidity and Dividend Policy have a significant effect on Stock Prices. In contrast, Profitability and Leverage do not have a significant effect. Simultaneously, the four independent variables significantly affect Stock Prices. This finding provides insights for investors and company management in making strategic decisions.